The dewaterability, heavy metal release and reuse characteristics of Golden Horn surface sediment - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
In this study the dewaterability, heavy metal release and reuse characteristics and reuse of Golden Horn surface sediment were investigated under remediation considerations. Determination of factors like specific resistance to filtration and moisture type of sediment is a prerequisite for rational selection of the most cost-effective volume reduction process. Twenty five percent and seventy five percent of the water content were of free and immobilized, and of bound nature, respectively, with a high resistance value revealing poor dewaterability characteristics. The leachate did not contain toxic heavy metals, even at pH 3. The sediment had strong adsorbability for Cu and Pb, and high buffering capacity. The reuse of the dried sediment as a clay mixture in brick manufacturing seemed possible up to 40 percent. Copyright (C) 1996 IAWQ.
Keywords: sediment; dewatering; metal adsorption and desorption; reuse; leachate; RESISTANCE; REDUCTION